(untitled) (Damu Journal of Sport Sciences, 2024)
Most of the previous methods in training the physical and skill variables of young players are done on grass or hard ground, and the problem of the research revolves around the lack of interest in the physical aspect that serves the skill aspect by trainers, in addition to the use of the second type of grass and dirt lands, as they are almost the common lands and widely used in clubs, and it has become common in training circles among trainers to use resistance exercises in their various ways and means, and therefore the use of the usual training methods does not serve the purpose effectively and quickly, which prompted the researcher to find a new training method in an attempt to enhance the development of these aspects, which is training on sandy ground as one of the resistance exercises, so the researcher decided to conduct a study to identify the effect of exercises on sandy ground in developing some physical variables and the achievement of 200m runners. The aim of the research is to: Prepare exercises using the sand field to develop Physical variables and the achievement of young 200-meter runners in Babylon Governorate. And knowing the duration of its effect. The most important conclusions were: 1-The use of training on sand contributed positively to the development of the studied physical variables (speed, strength, speed endurance, performance endurance, and achievement for young 200-meter runners. 2-Continuing training according to the exercises prepared by the researcher on sandy ground has enhanced the efficiency of the nervous and muscular systems to control, adapt, and organize the various processes that are compatible with the skill performance of young runners.